Breast Cancer Survivors’ Diet and Physical Activity Preferences and Barriers: How COVID-19 Changed the Intervention Landscape - Xin Chen; Chungyi Chiu; Helen Hoi Ting Cheung; Sylvia L Crowder; Xi Chen; Linda Trinh; Anna E Arthur (Current Developments in Nutrition)
Background: Existing studies on breast cancer survivors (BCS) have primarily focused on individual aspects of either diet or exercise preferences and barriers. Our study aims to examine BCS’ perceptions toward diet and exercise combined. Given the transformative impact of COVID-19, there is a crucial need for insights in the post-pandemic era to address the distinct challenges faced by BCS in maintaining their health and well-being. Objectives: This exploratory study aims to understand BCS’ preferences for and barriers to diet and exercise to inform future intervention development. Methods: A cross-sectional survey was administered to adults diagnosed with ductal carcinoma in situ or stage I–IV breast cancer (BC) from 2019 to 2021 regarding interest, preferences, and barriers to participating in diet and exercise interventions. Descriptive analysis compared pre-COVID-19 (pre-C) and during-COVID-19 pandemic (during-C) subsets. Results: There were 224 participants. Over half expressed interest in a BC research study related to diet and exercise. Most preferred receiving consultations in-person with relevant specialists, education or counseling in one-on-one sections, and information from written materials, in-person, or via technology. Barriers were fatigue, family, and work. One hundred and thirty participants completed the survey pre-C, and 94 during-C. Compared with pre-C, during-C participants preferred visual communication tools for information on nutrition and exercise over in-person methods (P < 0.05). In most categories, the percentage of barriers noted during-C was greater than pre-C. Conclusions: Participants indicated preference for dual-modal diet and exercise interventions. The pandemic impacted participation preferences and barriers, with shifts toward favoring visual communication tools over in-person services and increasing psychosocial and COVID-related barriers. Hybrid care, combining in-person with technology-based delivery, shows promise in enhancing flexibility and accessibility in nutrition and exercise interventions amid the pandemic.